Empowerment of MSMEs as a Strategy for Improving Welfare in the Indonesian Economic Context - Cucu Putria, Andien; Pratama, Gama (P3M - STAI Kuningan, 2023)
This research explores the role of empowering Micro, Small and Medium Enterprises (MSMEs) as a strategy to improve prosperity in the Indonesian economy. Through the literature study method, this research highlights the positive contribution of MSMEs to job creation, national income and economic inclusiveness. MSMEs have the potential to reduce unemployment rates by providing employment opportunities for vulnerable groups. Contribution to national income is seen through the creation of added value and economic diversification. Empowering MSMEs also positively impacts social aspects and community welfare, reducing disparities and strengthening local communities' social ties. Although promising, the challenges of financing access and global competition must be overcome. Policy recommendations include fiscal incentives, special financing facilities, and skills training programs. Indonesia can build a solid and inclusive economy by strengthening the role of empowering MSMEs.